The Simplified Medication Adherence Questionnaire: validation of a Brazilian-Portuguese version in hypertensive adults - Soares, Simony M.; Diniz, Mirela Q. de Almeida; Davino, Dilcy Morgana B. M. C.; Albieri, Fernanda B.; Santos, Adriano S.; Jesus, Elisdete M. S.; Lyra-Junior, Divaldo P.; Neves, Sabrina J.; Oliveira-Filho, Alfredo D. (Frontiers in Pharmacology, 2024)
Background: Self-reported adherence scales are widely used in research and practice because they are low cost and easy to apply. A free version in Brazilian-Portuguese of the SMAQ can be a useful alternative to determine the adherent behavior of hypertensive patients. Purpose: To translate and evaluate the psychometric properties of the Brazilian-Portuguese version of the Simpliﬁed Medication Adherence Questionnaire (SMAQ) therapeutic adherence scale for patients with arterial hypertension. Patients and methods: A multicenter cross-sectional study was conducted in five outpatient units in Maceió-AL and Aracaju-SE, between January and July 2019. 117 patients over 18 years, using antihypertensive drugs, were recruited. The cross-cultural adaptation followed international methodological recommendations. Internal consistency (Cronbach's alpha) was tested as a reliability parameter. Criterion and construct validity were verified by concurrent validation, exploratory factor analysis (EFA) and validation by known groups. Results: The participants had a mean age of 56.6 years (SD=10.7 years), most were female (72.6%). The mean number of antihypertensives prescribed per patient was 1.87 (SD=0.87). 79.5% (n=86) of patients were considered non-adherent. The internal consistency was satisfactory (Cronbach's alpha=0.63). A satisfactory correlation coefficient was verified with the Morisky-Green-Levine test as an external criterion (r=0.56 p<0.001). The scale's sensitivity measured through known group validity was 75.3%, specificity 29.5%, positive predictive value 63.9% and negative predictive value 41.9%. From EFA, we identified two factors of the instrument’s construct: specific medication-taking behaviours and barriers to adherence. The initial KMO measure of sampling adequacy was 0.691 and Bartlett’s test of sphericity was significant (χ2 = 118.342, p < 0.001).. Conclusion: The Brazilian-Portuguese version of the SMAQ scale proved to be valid and reliable for determining adherence to the pharmacotherapy in hypertensive patients. It showed more ability to detect non-adherent patients, but with low specificity, possibly influenced by high social desirability.